Fasting inhibits hepatic stellate cells activation and potentiates anti‐cancer activity of Sorafenib in hepatocellular cancer cells. Issue 2 (11th July 2017) - Lo Re, Oriana; Panebianco, Concetta; Porto, Stefania; Cervi, Carlo; Rappa, Francesca; Di Biase, Stefano; Caraglia, Michele; Pazienza, Valerio; Vinciguerra, Manlio
Abstract : Hepatocellular carcinoma (HCC) has a poor outcome. Most HCCs develop in the context of liver fibrosis and cirrhosis caused by chronic inflammation. Short‐term fasting approaches enhance the activity of chemotherapy in preclinical cancer models, other than HCC. Multi‐tyrosine kinase inhibitor Sorafenib is the mainstay of treatment in HCC. However, its benefit is frequently short‐lived. Whether fasting can alleviate liver fibrosis and whether combining fasting with Sorafenib is beneficial remains unknown. A 24 hr fasting (2% serum, 0.1% glucose)‐induced changes on human hepatic stellate cells (HSC) LX‐2 proliferation/viability/cell cycle were assessed by MTT and flow cytometry. Expression of lypolysaccharide (LPS)‐induced activation markers (vimentin, αSMA) was evaluated by qPCR and immunoblotting. Liver fibrosis and inflammation were evaluated in a mouse model of steatohepatitis exposed to cycles of fasting, by histological and biochemical analyses. A 24 hr fasting‐induced changes were also analyzed on the proliferation/viability/glucose uptake of human HCC cells exposed to Sorafenib. An expression panel of genes involved in survival, inflammation, and metabolism was examined by qPCR in HCC cells exposed to fasting and/or Sorafenib. Fasting decreased the proliferation and the activation of HSC. Repeated cycles of short term starvation were safe in mice but did not improve fibrosis. Fasting synergized with Sorafenib in hampering HCC cell growth and glucose uptake. Finally, fasting normalized the expression levels of genes which are commonly altered by Sorafenib in HCC cells. Fasting or fasting‐mimicking diet diets should be evaluated in preclinical studies as a mean to potentiate the activity of Sorafenib in clinical use. Abstract : Short‐term fasting (STS) cycles inhibit hepatic stellate cells activation and hepatocellular carcinoma cells proliferation in vitro. STS are harmless in an in vivo model of liver fibrosis. STS cycles might be promising approaches to treat liver diseases.